SOIL WETTING PATTERN OF SANDY LOAM SOIL IN RESPONSE TO DRIP IRRIGATION RUNNING TIME (FUDMA JOURNAL OF SCIENCES, 2023)
The wetting pattern of in-situ soil of sandy loam texture was evaluated under drip irrigation system with respect to the wetted diameter and depth in two locations. The drippers were run at the system’s predetermined maximum emitter discharge rate of 6.994 x 10-4 ls-1, with emission uniformity and optimum operating pressure of 95% and 172 KPa, respectively. The observed wetted diameter ranged between 19.2 cm and 22.8 cm at the National livestock project site, and 15.3 cm to 22.7 cm at the College of Forestry Mechanization research field within 15 to 75 minutes of irrigation. The observed values were compared with predicted values obtained from an existing model by means of correlation coefficient, agreement index and confidence index. The correlation coefficients showed a very high correlation (r = 0.70 – 0.90) for the observed and predicted wetted diameters and wetted depths at both sites. However, further analysis using the confidence index showed that there was bad correlation (c < 0.51) between the observed and predicted wetted diameters at both sites. The correlation between observed and predicted wetted depths at both sites showed excellent performance based on confidence index (c > 0.85). The study serves as a guide for irrigation scheduling under drip irrigation system as the root depth of the crop must at least be within the wetted volume (depth and area) of the soil. The study can be repeated with agricultural soils of other textures.
Keywords: Soil wetting pattern, sandy loam, drip irrigation, irrigation running time